Optimization of placebo use in clinical trials with systemic treatments for atopic dermatitis: an International Eczema Council survey‐based position statement. (12th March 2019) - Leshem, Y.A.; Bissonnette, R.; Paul, C.; Silverberg, J.I.; Irvine, A.D.; Paller, A.S.; Cork, M.J.; Guttman‐Yassky, E.
Abstract: Background: As novel systemic therapeutics for patients with atopic dermatitis (AD) are developed, ethical and methodological concerns regarding placebo‐controlled‐trials (PCT) have surfaced. Objective: To guide the design and implementation of PCT in AD, focusing on trials with systemic medications. Methods: A subgroup of the International Eczema Council (IEC) developed a consensus e‐survey, which was disseminated to IEC members. Results: The response rate was 43/82 (52%). Consensus was reached on 24/27 statements and on 3/11 options from multiple‐selection statements, including: performing monotherapy studies in proof‐of‐concept phases; avoiding concomitant topical corticosteroids or calcineurin inhibitors until a predefined timepoint as rescue (borderline consensus); selection of sites and assessors with recognized expertise in AD clinical trials; clear definition and identification of baseline disease severity; minimizing time and proportion of patients on placebo; using daily emollients with several options provided; instigating open‐label extension studies for enrolment after a predefined timepoint; and including outcomes which set a higher bar for disease clearance. Conclusion: Conducting PCT in AD requires balancing several, sometimes opposing principles, including ethics, methodology, regulatory requirements and real‐world needs. This paper can provide a framework for conducting PCT with systemic medications for patients with AD.